Prospective study of lignin-based and recycled carbon fibers in composites through meta-analysis of life cycle assessments. (20th June 2019) - Hermansson, Frida; Janssen, Matty; Svanström, Magdalena
Abstract: Screening the life cycle assessment literature for information and recalculating extracted results was proven useful for identifying environmental challenges and opportunities in new, but related, contexts at early stages of technology development. The method was applied to carbon fiber reinforced polymers, a material of growing importance in industrial applications where a strong and/or light material is needed, such as in aircrafts and road vehicles. Many technology development efforts with the purpose of further improving such composite materials are on-going, in particular regarding the origin of carbon fibers. Using lignin as a bio-based feedstock and various recycling techniques have been suggested. However, these technologies do not yet exist at a scale that would enable a meaningful life cycle inventory, while the need for environmental guidance is urgent in order to ensure that only the more promising development paths are pursued before lock-in occurs. With a specific focus on the shift to lignin as a feedstock for carbon fibers and on recycled carbon fibers in composites, this article not only illustrates the type of information that can be obtained from mining and refining information from earlier life cycle assessment studies, but it also provides direct guidance on environmental opportunities and challenges specific for carbon fiber reinforced polymers. Thereby, it informs both technology development efforts and environmental assessment efforts. Amongst other things, the analysis reveals that an important factor behind the environmental impact of composites is the energy demand in carbonization of the carbon fibers and that both the shift to lignin-based and to recycled carbon fibers can potentially reduce this environmental impact. However, assessments of both lignin (as an output from a multifunctional process) and recycled carbon fibers (as an output from end-of-life activities) are connected to challenges related to the allocation of environmental impacts in an environmental assessment. Extracting and refining information from the literature proved useful for the specific task but remains to be tested in other fields of emerging technologies. Highlights: Replacing materials with CFRP decreased energy use in less than half of the cases. The use of lignin as a raw material can decrease the impact of carbon fibers. Recycling carbon fibers was shown to decrease energy use significantly. Using recycled carbon fibers was more beneficial than using lignin as a raw material.